Representation and Anatomy of Anthropomorphic and Zoomorphic Dictionary Entries in the Russian-Croatian Phraseological Dictionary [2019] - Barčot, Branka (Poznańskie Studia Slawistyczne, 2021)
This paper presents the analysis of Russian animalistic phraseological units included in the Russian-Croatian Phraseological Dictionary (2019). In our research we focused on etalons that have the simile structure. Anthropomorphism and zoomorphism are two antipodes of the same reality within the language picture of the world – in our case it is the Russian language picture of the world. We believed that the anthropocentric perspective of the animal world was stronger than the ecocentric perspective, and that it has influenced the Russian language correspondingly, which has led us to the conclusion that there must be more Russian anthropomorphic similes than zoomomorphic similes. But the analysis that we have performed within the frames of the Russian-Croatian Phraseological Dictionary has not proven our hypothesis. The findings of this study suggest that there is an equal number of anthropomorphic and zoomorphic similes within the analyzed phraseological material.